Analysis of Interaction Between Interfacial Structure and Fibrinogen at Blood-Compatible Polymer/Water Interface - Ueda, Tomoya; Murakami, Daiki; Tanaka, Masaru (Frontiers in Chemistry, 2018)
The correlation between the interfacial structure and protein adsorption at a polymer/water interface was investigated. Poly(2-methoxyethyl acrylate)(PMEA), which is one of the best blood compatible polymers available, was employed. Nanometer-scale structures generated through the phase separation of polymer and water were observed at the PMEA/phosphate buffered saline interface. The interaction between the interfacial structures and fibrinogen (FNG) was measured using atomic force microscopy. Attraction was observed in the polymer-rich domains as well as in the non-blood compatible polymer. In contrast, no attractive interactions were observed, and only a repulsion occurred in the water-rich domains. The non-adsorption of FNG into the water rich domains was also clarified through topographic and phase image analyses. Furthermore, the FNG molecules adsorbed on the surface of PMEA were easily desorbed, even in the polymer-rich domains. Water molecules in the water-rich domains are anticipated to be the dominant factor in preventing FNG adsorption and thrombogenesis on a PMEA interface.